Climate Resilient Farming: Influence of Livelihood Assets on Agrochemical vs Organic Input Use in Coastal India - Roy, Sreejit; Sridev Adak; Saptarsi Chakraborty; Rishav Mukherjee; Mehedi Hasan; Muhammed M Irshad; Acharyya, Achiransu; Ghosh, Souvik (Indian Journal of Extension Education, 2025)
Climate change poses immense pressure on global agriculture, particularly in coastal regions. Several adaptation strategies to climate change were taken by farmers, though not all are aligned with long-term sustainability. Through logistic regression, the study assesses the role of livelihood assets in farmers’ choices between agrochemical intensification and organic farming, where livelihood assets were measured using the Department for International Development’s (DFID) framework. The study covered five coastal states and one coastal union territory of India. Using a stratified random sampling method, 520 agricultural households were surveyed during 2024–2025. Villages were selected based on proximity to the sea and the implementation of the National Innovation on Climate Resilient Agriculture (NICRA) and Project on Climate Resilient Agriculture (PoCRA) programmes. Findings indicate physical capital as a pivotal factor encouraging organic farming and curbing agrochemical intensification, while human capital reduces reliance on agrochemicals. Natural and financial capital enhance agrochemical use. The dual positive influence of social capital on organic farming and agrochemical intensification underscores the need for tailored guidance, as affirmed by sustainability-oriented initiatives, proven effective in limiting agrochemical intensification as NICRA and PoCRA. Inclusion in such programmes and enhancing human and physical capital may reinforce farmers’ orientation with sustainable adaptation trajectories. .